Pathologic Outcomes following Urethral Diverticulectomy in Women - Melissa A. Laudano; Asha E. Jamzadeh; Claire Dunphy; Richard K. Lee; Brian D. Robinson; Renuka Tyagi; Steven A. Kaplan; Alexis E. Te; Bilal Chughtai (Advances in Urology)
Purpose. Although most urethral diverticula in women are benign, there is a subset of patients who develop malignant changes. Limited studies report the pathologic findings associated with this relatively rare entity. We describe the clinicopathologic findings of women who underwent urethral diverticulectomy. Methods. A consecutive series of 29 women who underwent surgical resection of a urethral diverticulum were identified between 1992 and 2013. Clinical and radiographic data was collected by retrospective review of patient medical records. All pathological slides were rereviewed by a single urologic pathologist. Results. Of the 14 women with clinical data, 9 (64%) presented with urgency, 7 (50%) with urinary frequency, 3 (21%) with urinary incontinence, and 3 (21%) with dysuria. Mean diverticular size was 2.3 (±1.4) cm. Although one patient (3%) had invasive adenocarcinoma on final pathology, the remaining 28 cases (97%) demonstrated benign features. The most common findings were inflammation (55%) and nephrogenic adenoma (21%). Conclusions. Although most urethral diverticula in women are benign, there is a subset of patients who develop malignancy in association with the diverticulum. In this series, 97% of cases had a benign histology. These findings are important when counseling patients regarding treatment options.